2020
DOI: 10.1163/15685276-12341603
|View full text |Cite
|
Sign up to set email alerts
|

The Pilgrimage Landscape in Contemporary Estonia: New Routes, Narratives, and Re-Christianization

Abstract: This article is the first attempt at mapping the pilgrimage landscape in contemporary Estonia, reputedly one of the most secularized countries in Europe. Based on fieldwork on three case studies — the Estonian Society of the Friends of the Camino de Santiago, the Pirita-Vastseliina pilgrim trail, and the “Mobile Congregation” — we have identified three distinctive features that shape the Estonian pilgrimage scene. The processes of Caminoization and heritagization characterize pilgrimage on a European scale, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Coleman & Eade, 2004). It has been noted that the phenomenon of proliferation of regionally or nationally branded pilgrimage routes involves a fascinating process known as ‘caminoisation’ and ‘heritagisation’ of pilgrimage (Bowman & Sepp, 2019; Bowman et al, 2020; Coleman, 2019; Coleman & Bowman, 2019; Mikaelsson, 2019; Gemzöe, 2020; Johannsen & Ohrvik, 2020; Mikaelsson & Selberg, 2020; Sepp & Remmel, 2020). These new routes and the pilgrimage alongside them are formed and draw inspiration from the historical Camino de Santiago and align with the principles of heritage preservation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coleman & Eade, 2004). It has been noted that the phenomenon of proliferation of regionally or nationally branded pilgrimage routes involves a fascinating process known as ‘caminoisation’ and ‘heritagisation’ of pilgrimage (Bowman & Sepp, 2019; Bowman et al, 2020; Coleman, 2019; Coleman & Bowman, 2019; Mikaelsson, 2019; Gemzöe, 2020; Johannsen & Ohrvik, 2020; Mikaelsson & Selberg, 2020; Sepp & Remmel, 2020). These new routes and the pilgrimage alongside them are formed and draw inspiration from the historical Camino de Santiago and align with the principles of heritage preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars are avidly exploring how the inherent concepts of the Camino, with its spiritual significance and cultural richness, are harnessed to mould the character of these contemporary pilgrimages (Bowman et al, 2020; Bowman & Sepp, 2019). It should be noted, however, that these newer routes are not mere replicas but rather amalgamations of their own unique historical, cultural, and geographical elements, intricately interwoven to construct a narrative and pilgrimage practices that resonate deeply within the respective regions, as the case of the Nidaros Cathedral and the Fjord Pilgrim Route (Mikaelsson, 2019; Mikaelsson & Selberg, 2020; Johannsen & Ohrvik, 2020), and various emerging pilgrimage routes in Sweden (Gemzöe, 2020) and Estonia (Sepp & Remmel, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the range of organized religions, we should not ignore non-religious worldviews, the increasing presence of fluid and non-organized forms of religion (Uibu 2016), and individual religiosity (Altnurme 2018). Recent studies have shown that regardless of the apparent absence of interest in religion, phenomena connected to religion, such as pilgrimages (Sepp and Remmel 2020), belief in healers, or breathing techniques, have gained popularity in Estonia (Remmel and Uibu 2015).…”
Section: Religion In Estoniamentioning
confidence: 99%
“…Scholars have also examined the narratives, philosophy, literature, and depictions associated with pilgrimage and the social, cultural, and economic aspects of pilgrimage tourism. These studies contribute to our understanding of the diverse motivations, practices, and meanings of pilgrimage in different cultural and religious contexts (Alatas, 2019; Buitelaar, 2020; Buitelaar et al, 2020; Coleman, 2002; Feldman, 2014; Jafari and Scott, 2014; Nordin, 2009; Sepp and Remmel, 2020; Ulak, 2022).…”
Section: Introductionmentioning
confidence: 99%